Inovasi SAMPAH MAS (Sistem Pengelolaan dan Manajemen Sampah) Sebagai Solusi Pengelolaan Sampah Berkelanjutan - Adnan Adnan; Darmin Darmin; Sayafruddin Syafruddin (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This community service program aims to implement a sustainable waste management system based on appropriate technology in Kaboro Village, Lambitu District, Bima City. Through a participatory approach, this initiative involves target partners, including the Village-Owned Enterprise (BUMDES) and the Kaboro Village Government, in the education, design, and implementation of waste management tools, such as shredders and plastic incinerators, as part of sustainable waste management practices. The results of the activity demonstrate increased community awareness of the importance of waste management, as well as residents' ability to operate the tools independently after training. This program contributes to strengthening the circular economy, community empowerment, and achieving the Sustainable Development Goals (SDGs) at the local level. The activity also demonstrates that integrating simple technology with local wisdom can be a practical solution for plastic waste management.